2022
DOI: 10.1007/s00170-022-09878-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of CMT discontinuous wire arc additive manufacturing of Inconel 625

Abstract: Additive manufacturing (AM) is a progressive technology which holds promise for manufacturing of heat resistant super alloys. One of the most productive methods is wire arc additive manufacturing (WAAM). In this article, an alternative WAAM strategy is investigated. Experimental clads and material tests were performed to evaluate the material properties obtained through a cold metal transfer (CMT) discontinuous WAAM of Inconel 625 alloy. Using the modern terminology of Fronius Gmbh this method is called CMT cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Hardness measurements revealed no differences in hardness between samples from the CMT continuous WAAM strategy and those from the CMT discontinuous WAAM strategy. The results of the tensile strength tests unequivocally demonstrated that the mechanical properties of specimens from the CMT discontinuous WAAM strategy outperformed those from the CMT continuous WAAM strategy (Votruba et al , 2022).…”
Section: Study On Corrosion Resistancementioning
confidence: 93%
See 1 more Smart Citation
“…Hardness measurements revealed no differences in hardness between samples from the CMT continuous WAAM strategy and those from the CMT discontinuous WAAM strategy. The results of the tensile strength tests unequivocally demonstrated that the mechanical properties of specimens from the CMT discontinuous WAAM strategy outperformed those from the CMT continuous WAAM strategy (Votruba et al , 2022).…”
Section: Study On Corrosion Resistancementioning
confidence: 93%
“…Hardness measurements revealed no differences in hardness between samples from the CMT continuous WAAM strategy and those from the CMT discontinuous WAAM strategy. The results of the tensile strength tests unequivocally demonstrated that the mechanical properties of specimens from the CMT discontinuous WAAM strategy outperformed those from the CMT continuous WAAM strategy (Votruba et al, 2022). Table 6 indicates that different characteristics of corrosion behavior of Inconel 625 and the alloy have excellent hot corrosion resistance, fatigue resistance, wear resistance, weldability and high strength at elevated temperatures making it widely used in the aerospace, chemical, petrochemical, marine and high-temperature and corrosion applications industries (Kannan et al, 2021).…”
Section: Study On Corrosion Resistancementioning
confidence: 94%
“…The microstructure is porefree in both the as-deposited and heat-treated conditions. Owais Mansoor Inconel 625 [7] was deposited with good forming quality by using a layer-by-layer deposition strategy. Different microstructures were identified at the different layers of the specimen, with the bottom layers consisting mainly of fine primary cellular structures.…”
Section: Inconelmentioning
confidence: 99%
“…During welding, temperature variations in welds and parent metals have important effects on material characteristics and residual stresses, as well as on the dimensional and shape accuracies of welded products [6,7]. The CMT method has been effectively used for the welding and cladding of Inconel, Aluminum, Titanium alloys, steels, and other materials [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%